PUPILS' INTEREST IN PROFESSIONS IN TECHNOLOGY CLASSES FORMATION - Yusufxodjayeva F. M.; Maxmudova M. T. (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, as a result of the attention given to our national art in Uzbekistan, we should increase the sense of respect for our national values among young people, and contribute to the development of our national embroidery. it is taken into account that he acquires a decent profession, makes a valuable contribution to the development of society, lives and thereby manifests his identity in society, i.e. matures as a person. formation is aimed at.